Mad River - Sandford, John, 1944 February 23- (New York : G.P. Putnam's Sons, 2012)
Jimmy Sharp, Becky Welsh, Tom McCall. They were Bonnie and Clyde, they thought, and what's-his-name, the sidekick. Three teenagers with dead-end lives, and chips on their shoulders, and guns. The first person they killed was a highway patrolman. The second was a woman during a robbery. Then, hell, why not keep on going? As their crime spree cuts a swath through rural Minnesota, some of it is captured on the killers' cell phones and sent to a local television station. Bureau of Criminal Apprehension investigator Virgil Flowers joins the growing army of cops trying to run them down. But something doesn't feel quite right to him about the whole thing. He just hopes he can figure out what before too many people die. But even he can't realize what is about to happen next.
The next novel in the Virgil Flowers series.
Keywords: Flowers, Virgil (Fictitious character) -- Fiction; Government investigators -- Minnesota -- Fiction; Teenagers -- Fiction; Spree murderers -- Fiction; Large type boooks; Suspense fiction; Mystery fiction